Efeitos da preparação física sobre a performance global de atletas amadores de basquetebol universitário - Araújo, Thiago Machado de (2018)
Basketball is an intermittent, invasion team sport characterized by high intensity, hence, players need a good physical conditioning to perform actions of both physical and technical-tactical demands. However, unlike the favorable structure available to professional teams, amateur college teams face important limitations that interfere with training. In this way, the aggregate use of physical preparation and ball training (TCB) in the same training session seems to be a coherent methodological strategy that can optimize training time. This approach is understood as multicomponent training (MCT). However, it is not clear to what extent MCT interferes in the overall performance of athletes, i.e., not only physical abilities but also considering technical and tactical aspects of the game. So, this study aimed to evaluate the effects of the MCT on performance of athletes of a male amateur college basketball team. The sample consisted of eight amateur male basketball players (age: 22.7 ± 3.2 years, height: 180.8 ± 7.5 cm, body mass: 74.9 ± 4.7 kg) who were evaluated in three moments: Presentation, TCB and MCT, totaling 29 weeks of research. The TCB and MCT phases lasted 12 weeks with two weekly training sessions. Each session lasted 90 minutes. Two tests were used to measure the athletes' athletic ability: the Line Drill Test (LDT) and the Yo-Yo Intermittent Recovery Test Level 1 (Yo-Yo IR1). These tests provide information on anaerobic capacity, anaerobic performance reduction and aerobic power of athletes. For the measurement of the technical-tactical ability, three simulated games of four against four were used in the whole court, with duration of 10 minutes. The games were filmed for further analysis through the Basketball Technical-Tactical Individual Performance Assessment Tool – BB-PAT. Statistical analyzes were performed through descriptive statistics, ANOVA one-way of repeated measures, with post hoc of Bonferroni, and a significance level of 5% as parameter. Subsequently, the paired Student's T-test was performed to generate data that served as the basis for the inference analysis based on magnitude. Regarding the physical abilities, the athletes showed to be faster in the execution of the LDT (reduction of almost 2.5 s) and with a better aerobic conditioning (increase of 48.5%). In the technical-tactical capacities, the athletes progressed in the number of actions performed in the game (improvement of 14.16%), summation of points (30.62%), Adaptation DECs (28.49%), Decision Making, 10%), Efficacy (21.80%) and also in General Performance (23.44%). That is, after the intervention, the athletes not only presented an evolution in physical conditioning, but also transferred this improvement to the court, thus increasing their overall performance.